Lattice composite structures – current state of research and development in Russia and the world - A. A. Skleznev (Космические аппараты и технологии, 2024)
The paper provides an overview of the current state of research in the field of design and creation of anisogrid lattice composite structures – shell-type load-bearing structures – in Russia and abroad. Historical information about the emergence of lattice structures is provided, as well as a brief history of their formation – the research carried out, the results achieved, and the problems solved. An analysis of the use of mesh structures abroad in the aerospace industry was conducted. The paper provides generalized information on existing and currently used methods for designing anisogrid structures, applied methods for calculating mesh structures for strength, rigidity and stability, as well as on the main technological methods and techniques for manufacturing anisogrid lattice structures with a division into domestic and foreign practice. The paper presents information on current areas of application of lattice anisogrid structures in rocket technology, aviation and astronautics, and identifies a range of problematic issues and directions for future research. The work also provides examples of innovative applications of lattice anisogrid structures currently being developed, supplied with illustrations, and indicates the main scientific centers in Russia engaged in developments in the field of creation and production of composite lattice anisogrid structures.